Severe Cholestatic Hepatitis caused by Thiazolidinediones - Azar, Riad (2002)
Troglitazone maleate (Rezulin) has been associated with severe hepatotoxicity, which led to its withdrawal from the U.S. market in March 2000. Rosiglitazone maleate (Avandia) is being marketed as a safe alternative in the treatment of type 2 diabetes mellitus. We report a case of severe thiazolidinedione-induced cholestatic hepatitis in a 56-year-old female patient at a university hospital who was given rosiglitazone, 8 mg/day, after she developed milder hepatotoxicity while taking troglitazone. Rosiglitazone was discontinued, and the patient was treated with prednisone, azathioprine, and ursodiol. Clinical evaluation and liver biopsy were performed and liver function tests were monitored. After being switched from troglitazone to rosiglitazone the patient developed a severe cholestatic hepatitis with marked jaundice and moderate increases in serum alkaline phosphatase and γ-glutamyltranspeptidase but only mild increases in serum aminotransferases. Discontinuation of rosiglitazone and treatment with prednisone, azathioprine, and ursodiol led to improvement, albeit with residual injury, dropout of intrahepatic bile ducts, and persisting elevations of serum alkaline phosphatase. Rosiglitazone is not always a safe alternative in patients who have had hepatotoxicity to troglitazone. It is important to monitor the serum alkaline phosphatase in addition to the serum aminotransferases in patients taking thiazolidinediones.